2007
DOI: 10.1128/aem.01510-07
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Insecticidal Activity against Resistant Culex quinquefasciatus Mosquitoes by Expression of Chitinase Gene chiAC in Bacillus sphaericus

Abstract: Expression of a chitinase gene, chiAC, from Bacillus thuringiensis in B. sphaericus 2297 using the binary toxin promoter yielded a recombinant strain that was 4,297-fold more toxic than strain 2297 against resistant Culex quinquefasciatus. These results show that this chitinase can synergize the toxicity of the binary toxin against mosquitoes and thus may be useful in managing mosquito resistance to B. sphaericus.Insects of dipteran species such as Culex spp., Anopheles spp., and Aedes spp. are responsible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The latter explanations may hold true for the native Bt 55 strain described in this study, which had enhanced mosquitocidal activity, a similar cry and cyt gene profile as that of Bti -H14, but also possessed the Chi gene. The chitinase gene has been shown to elevate the mosquitocidal effect by perforating the peritrophic membrane, thereby increasing the accessibility of the Cry and Cyt toxins to receptors on the epithelial membrane [7, 47]. Abdullah et al [48] further experimentally demonstrated that transferring the chitinase gene from B. subtilis to a Bt strain improved its insecticidal bioactivity.…”
Section: Discussionmentioning
confidence: 99%
“…The latter explanations may hold true for the native Bt 55 strain described in this study, which had enhanced mosquitocidal activity, a similar cry and cyt gene profile as that of Bti -H14, but also possessed the Chi gene. The chitinase gene has been shown to elevate the mosquitocidal effect by perforating the peritrophic membrane, thereby increasing the accessibility of the Cry and Cyt toxins to receptors on the epithelial membrane [7, 47]. Abdullah et al [48] further experimentally demonstrated that transferring the chitinase gene from B. subtilis to a Bt strain improved its insecticidal bioactivity.…”
Section: Discussionmentioning
confidence: 99%
“…quinquefasciatus (Cai et al, 2007). These results show that chitinase can synergize the toxicity of Bin and thus may be useful in managing larval resistance to B. sphaericus .…”
Section: Recombinant Strainsmentioning
confidence: 99%
“…Some virulence factors enhance the insecticidal activity of the Cry protein by destroying the epithelial cells of the insect midgut. For example, an enhancing‐like protein Bel1 can enhance the toxicity of Cry1Ac by degrading the peritrophic matrix (PM) and intestinal mucin (IIM) of Trichoplusia ni and Helicoverpa armigera larvae midguts (Fang et al ., ); chitinases produced by B. thuringiensis can increase the activity of Cry proteins against different insect targets (Tantimavanich et al ., ; Cai et al ., ); an M4 metalloproteinase Bmp1 is toxic to Caenorhabditis elegans and exhibits intestinal tissue degradation activity to enhance the toxicity of Cry5Ba against C. elegans (Luo et al ., ). Meanwhile, some virulence factors may facilitate better germination and colonization of B. thuringiensis in insects.…”
Section: Introductionmentioning
confidence: 99%